Synthesis and Characterization of ZnO Nanoparticles Using Sol-Gel Method - Ningsih, Sherly Kasuma Warda; Khair, Miftahul; Veronita, Silvi (Universitas Negeri Semarang, 2021)
ZnO nanoparticles have many applications in photocatalysis. The sol-gel technique is one of the lowest-cost and easy-to-perform methods for synthesizing ZnO nanoscale. The purpose of this study was to determine the effect of precursors on the characteristics of the ZnO nanoparticles obtained by using the sol-gel method, including examining the purity of ZnO nanopowder, crystal structure/size, and morphology. ZnO nanopowder was prepared using zinc acetate dihydrate, zinc chloride, and zinc sulfate heptahydrate as various precursors, and calcination was carried out at temperatures of 400 and 600Ã‚Â°C. ZnO nano powder was characterized by Energy Dispersive X-Ray Fluorescence (ED-XRF), X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM). ED-XRF data shows that the highest purity of ZnO is 97.2% using zinc acetate dehydrate precursor. The precursors greatly influence the crystal structure and size of the ZnO nanopowders. In this study, the XRD ZnO pattern shows the hexagonal structure (wurtzite) with the crystal size of the ZnO nanopowders is 37-84 nm. Temperature variations affect the structure and morphology of ZnO powder. SEM micrographs of ZnO nanopowders are small spherical and twig-like agglomerations.